THE ROLE AND IMPORTANCE OF DETERMINISTIC COMPUTER SIMULATIONS IN THE DEVELOPMENT OF TECHNICAL CREATIVITY - Prauzner, Tomasz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The deterministic computer simulations (abbr. DSK) are a group of simulation software most often used in the process of technical education. Innovative education based on the introduction of this group of software into the online and offline learning process creates a new work environment conducive to creativity and creativity in humans. This article presents theoretical discussions as well as the place and role of DSK among modern teaching aids.